CodeX effectively identifies high-risk patients with asthma or COPD in Dutch primary care, supporting guideline-driven treatment - Iris van Geer-Postmus; Marika T. Leving; Yoran H. Gerritsma; Esmé Baan; Lars Dijk; Evelien Harms; David Price; Gerian H. Prins; Jennifer K. Quint; Dermot Ryan; Philippe Salomé; Björn Ställberg; et al. (Therapeutic Advances in Respiratory Disease)
Background: Prevention of lung attacks (LAs)/exacerbation is an important treatment goal in both asthma and chronic obstructive pulmonary disease (COPD). However, LAs are often not registered as such in medical records. Objectives: Development and evaluation of CodeX Asthma and COPD. Design: An electronic medical record-based algorithm to identify LAs in Dutch primary care patients with asthma or COPD was developed. The algorithms were evaluated in nine general practices in the Netherlands. Results: A total of 479 LAs (in 1164 patients) were identified with CodeX Asthma in the past year, of which only 16% were registered. CodeX COPD identified 321 LAs (in 242 patients) in the past 3 years, of which two were registered. Conclusion: CodeX algorithms are capable of identifying unrecorded LAs and high-risk/uncontrolled patients in an easy way. This offers primary care providers a simple solution to easily identify and closely manage high-risk patients with asthma or COPD by identifying LAs’ frequency and potential under- or overtreatment.